Converged play characteristics for early childhood education: multi-modal, global-local, and traditional-digital. (2nd September 2020) - Edwards, Susan; Mantilla, Ana; Grieshaber, Susan; Nuttall, Joce; Wood, Elizabeth
ABSTRACT: This paper discusses characteristics of converged play for early childhood education. The characteristics were derived from a four-year study of teachers' interpretation and use of 'web-mapping' as an explicit conceptual tool, designed to mediate teaching practices and learning outcomes according to a definition of pedagogy as the relationship between teaching and learning. Three characteristics of converged play were identified via detailed analysis of ten core converged play 'episodes' drawn from teacher exemplar cases. The characteristics were 'multi-modal', 'global-local', and 'traditional-digital'. The characteristics of converged play presented can help teachers understand teaching and learning in the digital age, providing a starting point for an early childhood pedagogy in which children and teachers can engage in well-established opportunities for play-based learning alongside multi-modal, global-local, and traditional-digital activities in early childhood education and care settings.